Analysis of the association between Healthy Eating Index (HEI)-2020 and diabetic kidney disease in type 2 diabetes patients: Based on the NHANES database. - Dong, Chunping; Li, Hui; Li, Jing; Qiao, Yuan; Gao, Shan (Nefrología, 2026)
Background: A rise in the Healthy Eating Index (HEI) 2020 is associated with a reduced risk of chronic kidney disease. However, it remains unclear whether HEI-2020 exhibits a similar positive effect in diabetic patients. Objectives: This work aimed to investigate the relationship between HEI-2020 and the prevalence of diabetic kidney disease (DKD) in type 2 diabetes (T2D) patients. Methods: A cross-sectional analysis was based on the National Health and Nutrition Survey database from 2007 to 2018. A weighted logistic regression model, restricted cubic splines, and subgroup analysis were undertaken to assess the relationship between HEI-2020 and the prevalence of DKD in T2D patients. A weighted logistic regression model and a weighted quantile sum (WQS) regression model were employed. The independent impact of HEI-2020-related components on the prevalence of DKD among T2D patients was analyzed. In addition, sensitivity analysis was conducted. Results: A total of 4255 participants with T2D were enrolled, with a DKD prevalence rate of 34.7%. The logistics regression analysis demonstrated a significant inverse relation between the HEI-2020 score and the prevalence of DKD in fully adjusted models (OR = 0.982, 95% CI: 0.973-0.992, P < 0.001). No nonlinear relationship was detected (P-non-linear = 0.970). No subgroup with significant interaction was identified. The WQS regression indicated that in fully adjusted models, the WQS index for HEI-2020 was significantly negatively correlated with the prevalence of DKD among T2D patients (OR = 0.765, 95% CI: 0.621-0.943, P = 0.012), with dairy products, total protein foods, and total vegetables as the most influential components. In addition, HEI-2020 was significantly negatively correlated with DKD in previously diagnosed T2D patients (OR = 0.979, 95% CI: 0.967-0.990, P < 0.001), while no significant association was observed in newly diagnosed patients. The sensitivity analysis yielded similar results, indicating that our results were robust. Conclusion: This research revealed a relationship between an increase in the HEI-2020 score and a lower prevalence of DKD among T2D patients, emphasizing the importance of the intake of dairy products, total protein foods, and total vegetables. This finding provides new scientific grounds for dietary management in T2D patients.